Improvement Of Stocatic Optimization In Detection Of Driving Drivers Movement On Avi Video Type Using Mathlab - SOLLY ARYZA (INFOKUM, 2021)
Vehicle users sometimes do not pay attention to the safety and security of the environment by driving at very high speeds. This is exacerbated by moving that is not by the rules, making it prone to accidents. Detection of the motion of an object in the avi video this time is focused on the operation of detecting the area of ​​moving objects in the avi video. The operation used in processing the detection of an object is an operation on image processing because the video is a collection of images executed in a unit of time. For this reason, this method works by getting information from a video.